A relação profissional-paciente em um programa de reabilitação de pessoas com deficiência física - Pereira, Maíra Baldan Fechio Rodrigues (2015)
Through this study we sought to investigate the relationship health professional and patient with physical disabilities from the perception of professionals working in care in a physical rehabilitation program. Initially a review of concepts related to health was conducted; humanization concepts; Physical Rehabilitation; and theoretical concepts from theories focused on the issue of care and therapeutic bond. Seconded theorists in the study are Michael Balint and John Bowlby. The two authors were eminent psychoanalysts who have dedicated themselves to the study of human relations and more specifically, each in his own way, aspects of the bond in care relations. Later was presented the survey of 11 health professionals (social workers, psychologists, nurses, physiotherapists, speech therapists, nutritionists). The professionals participated in a semi-structured interview, focusing on issues relevant to theme. From this information contained in the speech of this group was able to discuss some important issues involved in this practice. Most individuals values listening, acceptance and empathy as important qualities and resources for the therapeutic encounter.. The academic internship experience is seen as an important tool for the preparation and training of professional, with regard to its contact with the patient, but most complained about the lack of larger space in the academic discussion related to the theme of professional-patient relationship, that all value as important to the quality of the performance and effectiveness of the service. The relationship established with patients, is for these professionals a help of offering opportunity to the next and also of growth and appreciation of life itself. However, they also report that often identify the emergence of fears, anguish and suffering before the sharing of patient experience. The group refers fears about their health and physical and mental integrity. Of these highlighted difficulties in dealing with the institutional aspects, the relationships between professionals and hierarchies, lack of time and workload. Shines the spotlight awareness of the need for health professionals to adopt measures and actions to ensure their own health in a comprehensive way, but through its investments you can see that part of these precautions are overlooked or excluded from their daily health care practices . Given the emotional impact many seek help and support with the spirituality, the contact with their families, friends and co-workers, but reinforce that participation in a structured and focused activity on this theme would offer a better personal resources development opportunity for more adequately cope with these subjective aspects that often find no room for discussion and elaboration in everyday reality. The speech expressed by this group of professionals does not allow generalizations, however justify the need for future studies and draws attention to the need for structuring resources and tools for many health professionals can develop and offer quality care through which can contribute even more effectively with the health of patients, while considering their own health and integrity